PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE (GCG) PADA NILAI PERUSAHAAN (Studi Pada Perusahaan Yang Masuk Indeks LQ45 Di Bursa Efek Indonesia) - Zanera Saroh Firdausya; Widyar Effendi (JWM (JURNAL WAWASAN MANAJEMEN), 2013)
This study aimed to analyze the effect of managerial ownership, institutional ownership, board size, independent board size, board size and the size of the value of the company on the companies included in the LQ 45 index in Indonesia Stock Exchange. The sampling method used was purposive sampling. Of the population of firms that enter in LQ 45 during the period of 2009-2011, taken nineteen sampel. Alat companies that meet the criteria of analysis used is multiple linear regression analysis by first covering the classical assumption of normality test, multikolonieritas, autocorrelation, heteroskedasticity. The results showed a significant variable that is partially managerial ownership. While the variable institutional ownership, board size, board size independent, board size and size has no effect on firm value.